Information, Innovation, and Behavior: Powering ICT-Mediated Extension - Spielman, David J. (2019)
David J. Spielman COUNTRY WORKSHOP The Knowledge Lab on Climate Resilient Food Systems: An analytical support facility to achieve the SDGs Co-Organized by IFPRI and AGRA FEB 7, 2019 - 08:30 AM TO 05:55 PM EAT